Developing Local-Based Education through the Coastal Children Nature School Program to Enhance Coastal Community Empowerment - Maulida Nur Faticha; Vrisco Harjanto; Zahit Idris (Prospect Publishing, 2026)
Limited access to education, low literacy levels, and limited environmental awareness remain major challenges for coastal community development. To address these issues, the Coastal Children's Nature School (Sekolah Alam Anak Pesisir) was established in Cendi Manik Village, Sekotong District, West Lombok Regency, as a community-based non-formal education initiative integrating education, environmental conservation, and local economic empowerment. This study describes the implementation of the program through a local-based educational approach that incorporates the principles of Education, Ecology, and Economy (3E). The program adopts place-based, experiential learning by using the Bagek Kembar Mangrove Ecotourism Area as a natural learning laboratory. Its implementation is supported by a multi-stakeholder partnership involving PT Pertamina Patra Niaga Integrated Terminal Ampenan through its Corporate Social Responsibility (CSR) program, Sanggar Belajar Jalan Pulang, the Bagek Kembar Tourism Awareness Group (POKDARWIS), universities, the village government, and community organizations. The program has improved students' literacy, numeracy, communication skills, environmental awareness, character development, and entrepreneurial mindset while strengthening family engagement, local institutional capacity, and cross-sector collaboration. These findings demonstrate that the program provides a replicable community-based education model that promotes sustainable coastal development by integrating education, mangrove conservation, and community empowerment.